Analyzing Business Strategies of Ayam Nelongso Using EFAS and IFAS: A Case Study of Culinary - Mahendra, Rifqi Dwi; Hari Mulyadi; Dian Herdiana Utama (Ebisma (Economics, Business, Management, & Accounting Journal), 2024)
Ayam Nelongso is a fast-food business that excels in offering affordable prices, distinctive flavors, and strong customer loyalty. However, to sustain growth amidst fierce competition and shifting consumer preferences, Ayam Nelongso must address operational weaknesses and leverage opportunities in digitalization and product diversification. Using the Triple Layered Business Model Canvas (TLBMC) approach, the integration of economic, social, and environmental aspects is analyzed to develop a holistic and sustainable strategy. The economic layer focuses on improving operational efficiency and market expansion through digitalization. The social layer emphasizes community engagement and customer experience, while the environmental layer highlights the adoption of eco-friendly practices. The integration of these layers demonstrates that with the right innovation and adaptation, Ayam Nelongso can maintain its economic performance while meeting modern consumer needs and contributing to sustainability.